Lactate concentration comparison between 100m freestyle and tethered swimming of equal duration - Thanopoulos, V.; Rozi, G.; Platanou, T. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Maximum capacity of anaerobic lactic mechanism is proportional to the production of lactic acid. One of the most common test is the 100 meters freestyle. Many researchers have used tethered swimming to measure aerobic and anaerobic capacity (Maglischo, 2003). The question created is with which test of 100m freestyle or the tethered swimming, both at the same time, can achieve maximum accumulation of lactic acid in blood. The aim of this research is to compare lactic acid production in both tests of maximum effort and equal time: a) in 100 meters freestyle and b) in tethered swimming. METHODS: In this study participated 12 swimmers of national level (age=21.5±0.67 years, Body stature =181.8±7.24 cm and Body mass=80.75±7.99 ). At the beginning, they swam 100 meters freestyle with maximum intensity and time performance and blood lactate accumulation were measured. Afterwards, in two days time the same athletes were tested in tethered swimming, in equal time to that they achieved in 100 meters (Bonen et al.,1980). In order to determine maximum concentration of lactic acid in the two different tests, samples of blood were taken in 3rd, 5th, and 7th minute of recovery time. RESULTS: The average maximum accumulation of lactic acid in 100 meters freestyle was 11.09 ±4.22 mmol/l, while in tethered swimming 10.27 ±3.29 mmol/l. The average time performance in 100 meters freestyle as well as in tethered swimming was 58.74 ±2.33sec. There was statistical significant correlation between performance time of 100m freestyle and mean strength in tethered swimming (r= -0.63, p< 0.05), while no significant correlation was found between performance time in 100m freestyle, mean strength in tethered swimming and maximum accumulation of lactic acid. DISCUSSION: From the results it is obvious that both tests are adequate for the evaluation of maximum capacity of anaerobic lactic mechanism, with a difference as far as it concern the maximum accumulation of lactic acid. The tethered swimming test comes behind the 100 meters freestyle test in lactic acid production, probably because it influences the technique of legs in freestyle and as a result the rhythm and the intensity of the effort are reduced.